To determine the constant rate of change from the given points (0, 3) and (-2, -1), we can use the formula for slope (rate of change):
\[ \text{Rate of Change} = \frac{y_2 - y_1}{x_2 - x_1} \]
Using the points (0, 3) and (-2, -1):
- Let (x1, y1) = (0, 3)
- Let (x2, y2) = (-2, -1)
Now, substituting into the formula: \[ \text{Rate of Change} = \frac{-1 - 3}{-2 - 0} = \frac{-4}{-2} = 2 \]
So, the information Sekou was likely given would be filled in as follows:
The initial value of the function is 3
The function has a constant rate of change equal to 2.